(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The significance of the research was crystallized in assisting football players in developing their endurance, speed, and performance through modern training methods (high frequency and Crossfit) and determining which of the two methods is superior in developing the variables under study. The modern methods (High-Intensity Frequency and Crossfit) are among those that work on developing these variables, which have been widely used in recent years due to their importance in improving performance levels. The research problem can be divided into two main axes. First, a low level of special endurance is associated with and affects the players’ performance in the final stages of a match, especially due to changing conditions from attack and defence. The second axis is some coaches’ failure to use effective and efficient training methods appropriate for the nature of the game. Research objectives include preparing high-intensity repetitive and cross-fit exercises, identifying the effectiveness of high-intensity repetitive and cross-fit exercises in developing special endurance in football players, and comparing the effectiveness of the two experimental groups in developing special endurance. As a result of the high-intensity frequency method and cross-fit exercises used by the first and second experimental research groups, the researchers concluded that they developed their endurance through the exercises. According to the post-test results between the two groups, a preference for the high-intensity frequent method for special endurance exercises has been found. Based on the conclusions reached by the researcher, football coaches should pay great attention to training methods that suit football players because they enhance young football players’ endurance. In addition, for young football players with ball feet, the frequent high-intensity method is more effective than cross-fit in developing special endurance. The method of high-intensity repetitions in developing special endurance is more effective than cross-fit in developing the special endurance of young football players.